Kepemimpinan dalam Iman : Otniel Sebagai Teladan Pemimpin Bagi Mahasiswa Teologi : Hakim-Hakim 3:7-11 - Sah Rejeki Sinamo; Simpan Pahimpu Pardede (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The Book of Judges describes a period in Israel’s history marked by disobedience to God, leading to oppression by the enemy. In this context, Othniel appears as a judge appointed by God to free the Israelites. His leadership not only functions in a military aspect, but also as a spiritual director who brings the people back to obedience. Through the story of Othniel in Judges 3:7-11, this article explores the theme of leadership in faith, emphasizing the importance of a strong relationship with God and the anointing of the Spirit in leading. This story emphasizes that a true leader is able to inspire a community to turn to God, making him a role model for theology students in living out their calling. This study provides insight into how faith-based leadership can bring healing and stability to communities facing spiritual challenges.